Overexpression of malic enzyme isoform 2 in Chlamydomonas reinhardtii PTS42 increases lipid production. (September 2019) - Kim, Jongrae; Kwak, Ho Seok; Sim, Sang Jun; Jin, EonSeon
Abstract: Genetic modification of microalgae has been performing to overcome the economic and technical difficulties associated with biodiesel production. In this study, to explore a new approach to exploiting a metabolic pathway for effective lipid production, we engineered Chlamydomonas reinhardtii PTS42 to overexpress malic enzyme isoform 2 ( ME2 ) which catalyzes the conversion of malate to pyruvate. Overexpression of ME2 resulted in increase of mRNA level (around 2–3 fold) and increase of the pyruvate content (42.4% and 44.8% respectively) in transgenic M16 and M17, respectively. The fatty acid content and the lipid content of M17 were increased by 23.4 and 19.9% respectively compared to parental lines under the nitrogen deprivation condition. However, no significant changes in fatty acids composition was observed in transgenic lines. These results demonstrate that ME2 overexpression enhances the availability of pyruvate for fatty acid biosynthesis and lipid production in C. reinhardtii . Highlights: Malic enzyme 2 was successfully overexpressed in Chlamydomonas reinhardtii . Overexpressed malic enzyme 2 increases intracellular pyruvate concentration. Overexpressed malic enzyme 2 enhances total fatty acid content in Chlamydomonas .